'I make the rules on my Wall': Privacy and identity management practices on Facebook. (February 2016) - Georgalou, Mariza
Much significant work on the topic of privacy and identity on social network sites (SNSs) stems from the realms of media, information and cultural studies, and sociology eschewing language-based disciplines almost entirely. To redress the balance, this article draws on discourse-centred online ethnography, an approach which blends online ethnography with discourse analysis, to explore how self-presentation on Facebook is regulated by means of privacy. To this end, I analyse a dataset of statuses, comments, links, photographs and interviews from five Greek users. The findings highlight users' creativity and criticality in combining software affordances with linguistic signals and textual practices to manage their privacy and hence their identity.